2022
DOI: 10.1128/spectrum.01674-22
|View full text |Cite
|
Sign up to set email alerts
|

Immune Response to Conjugates of Fragments of the Type K9 Capsular Polysaccharide of Acinetobacter baumannii with Carrier Proteins

Abstract: Immunization by glycoconjugates with A. baumannii type K9 CPS fragments induced a high level of antibodies (predominantly IgG) in sera, which reacted specifically with the CPS of A. baumannii type K9, as well as a long immunological memory. The sera of immunized animals efficiently opsonized A. baumannii type K9.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…To obtain monoclonal antibodies, we immunized mice with a conjugate synthesized by squaric-acid chemistry which included bovine serum albumin (BSA) and a fragment of two oligosaccharide repeats (K-units) of A. baumannii type K9 CPS. As shown earlier, immunization with this conjugate provides a high titer of specific antibodies in blood serum ( 6 ), indicating the formation of a sufficient pool of plasma cells to obtain hybridoma cell lines which stably produce MAbs. Splenocytes and cells of the popliteal lymph nodes were used as a source of lymphocytes for hybridomas secreting MAbs against the K9 CPS according to the methods of Kоller and Milstein ( 8 ).…”
Section: Resultsmentioning
confidence: 57%
See 2 more Smart Citations
“…To obtain monoclonal antibodies, we immunized mice with a conjugate synthesized by squaric-acid chemistry which included bovine serum albumin (BSA) and a fragment of two oligosaccharide repeats (K-units) of A. baumannii type K9 CPS. As shown earlier, immunization with this conjugate provides a high titer of specific antibodies in blood serum ( 6 ), indicating the formation of a sufficient pool of plasma cells to obtain hybridoma cell lines which stably produce MAbs. Splenocytes and cells of the popliteal lymph nodes were used as a source of lymphocytes for hybridomas secreting MAbs against the K9 CPS according to the methods of Kоller and Milstein ( 8 ).…”
Section: Resultsmentioning
confidence: 57%
“…Previously, the authors have shown that immunization with conjugates of CPS fragments via protein carriers stimulates and induces protective immune reactions and protects model laboratory animals against infection by A. baumannii ( 6 ). In this work, MAbs against the K9 capsular polysaccharide of A. baumannii were prepared by immunization with a glycoconjugate that contained a K9 CPS fragment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunizing mice with the conjugate induced high levels of IgG antibodies in serum and stimulated the production of IL-10, IL-17A, and TNF-α. Mice immunized with the conjugate together with Freund’s adjuvant and calcium phosphate adjuvant, had 100% and 70% survival after stimulation with A. baumannii , respectively ( 50 ). Li et al.…”
Section: Candidate Subunit Vaccines For Acinetobacter Bauma...mentioning
confidence: 99%
“…Freund’s adjuvant is a water-in-oil emulsion that can cause granulomas and have other adverse effects after injection, so it cannot be used in the manufacture of human vaccines ( 148 ). Freund’s adjuvant is still widely used in animal experiments because of its strong adjuvant effect and affordable cost ( 27 , 50 , 149 ). MF59 and AS03 are oil-in-water adjuvants that overcome the shortcomings of Freund’s adjuvant and are effective adjuvants in many vaccines.…”
Section: Adjuvantsmentioning
confidence: 99%